Pendidikan Islam Perspektif Manajemen - Eriyanto, Eriyanto; Junaidi, Junaidi (Program Pascasarjana Universitas Ibrahimy, 2018)
Education in Islam should be managed as well as possible. Management of Islamic education is one way to improve the quality of people's lives from backwardness both morally, materially, and spiritually. In Islam, management is very important. This is seen by wise expression